Girard and Theology. - Kirwan, Michael (Everyman's library. Theology & philosophy., 2009)
The work of the French American theorist René Girard (b.1923) has been highly influential in a wide variety of intellectual disciplines. One enthusiastic reviewer in Le Monde suggested that the year 1972 (when La Violence et le Sacré was published) should be marked with an asterisk in the annals of the humanities, including literature, theology and religious studies. There is a paradox here insofar as Girard is, strictly speaking, neither a philosopher nor a theologian. He was trained as a historian, but spent most of his academic career as a teacher of French literature. It is out of his stud.